Strategi Pemasaran Digital Budidaya Ikan - Anggi Ramadan Kurniawan; Ragil Timur; Muhammad Naufal Miftahul Hakim; Tata Sutabri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the current digital era, traditional marketing has transformed into digital marketing. One sector that can take advantage of this change is the fish farming sector, especially catfish. This article outlines various digital marketing strategies that can be implemented to increase sales and brand awareness of catfish farming. Catfish farming has become one of the fastest-growing fishing industries, and with the development of digital technology, online marketing has become an important strategy to achieve success in the catfish farming business. This article presents a journal about digital marketing strategies in catfish farming, which includes research, experience, and guidance for utilizing digital platforms to increase the success of the catfish farming business